ChemInform Abstract: An Old Dog with New Tricks: Schiff Bases for Liquid Crystals Materials Based on Isoxazolines and Isoxazoles. Issue 25 (June 2016) - Fritsch, Luma; Merlo, Aloir A.
Abstract: A collection of Schiff bases derived from isoxazolines and isoxazoles is synthesized.